FAKTOR KUNCI KEBERHASILAN IMPLEMENTASI STRATEGI : STUDI KASUS PROGRAM DIGITALISASI ADMINISTRASI DI SMK NEGERI 2 SANGATTA UTARA - Phiniel Kurung Pabita; Nanda Putri Amelia Santoso; Siti Novi Coalliani; Laila; Dini Aulia Mahmud; Widyatmike Gede Mulawarman; Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the key factors influencing the success of administrative digitalization implementation at SMK Negeri 2 Sangatta Utara. A mixed-method approach with an explanatory sequential design was employed, involving questionnaire data from 163 respondents and in-depth interviews with selected key informants. The examined variables include management support, human resource competence, technological infrastructure, system suitability, and user acceptance. The results of multiple linear regression analysis indicate that all five variables significantly affect the success of administrative digitalization, with user acceptance emerging as the most dominant factor (β = 0.341). The adjusted R² value of 0.684 demonstrates that the model explains 68.4% of the variance in digitalization implementation success. These findings highlight the importance of integrating technical and human aspects in digital transformation and provide strategic recommendations for schools to strengthen administrative digitalization in order to enhance the effectiveness of educational governance.